Transnational death and technological haunting - Sánchez-Querubín, Natalia (Frontiers in Human Dynamics, 2023)
The paper proposes ‘technological haunting’ as a concept in digital migration and transnational death studies. Existing theory and empirical work in media studies explore connections between new media and grieving practices and how affordances of co-presence and portability shape how people maintain bonds with the deceased. The unique considerations that ‘technological haunting’ brings to the study of transnational families and death still need to be addressed by both media scholars and researchers within digital migration studies.